SISTEM PENENTU GERAKAN MOBILE ROBOT YANG BELAJAR SENDIRI CARA UNTUK BERGERAK MAJU DAN MENGINDARI TRABRAKAN MENGGUNAKAN NEURAL NETWORK (NN) - Puspita, Eru (LPPM Universitas Terbuka, 2011)
Commonly used for driving mobile robot is by using certain pre defined algorithm. This research will try to develop driving technique using continuous self learning NN while mobile robot on go. This research only observe about how mobile robot by it self can move forward an how to avoid a collision. Program NN will try to learn how to move forward, backward, turn left, turn right or other possibility depend on or by using collision experience. The test results obtained 82% successful runs forward and approximately 90% managed to avoid a collision.